Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.0022-1821.2005.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Expert Reviews on Consumer Demand for Experience Goods: A Case Study of Movie Critics*

Abstract: An inherent problem in measuring the influence of expert reviews on the demand for experience goods is that a correlation between good reviews and high demand may be spurious, induced by an underlying correlation with unobservable quality signals. Using the timing of the reviews by two popular movie critics, Siskel and Ebert, relative to opening weekend box office revenue, we apply a difference-in-differences approach to circumvent the problem of spurious correlation. After purging the spurious correlation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
314
0
13

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 446 publications
(353 citation statements)
references
References 40 publications
15
314
0
13
Order By: Relevance
“…Persuasive power has been explored in the domains of movies [18], e-commerce [20], advertising [23], and news [19]; however, there has been little investigation into the effect on player experience. Jenkins et al [8] studied the effects of showing a high, low, or no game score to players.…”
Section: Related Workmentioning
confidence: 99%
“…Persuasive power has been explored in the domains of movies [18], e-commerce [20], advertising [23], and news [19]; however, there has been little investigation into the effect on player experience. Jenkins et al [8] studied the effects of showing a high, low, or no game score to players.…”
Section: Related Workmentioning
confidence: 99%
“…Most researchers have identified a positive relation between the critics' judgments and box office success (e.g., Litman, 1983;Litman & Kohl, 1989;Sawhney & Eliasberg, 1996;Sochay, 1994). Nonetheless, some investigators have found no relationship (Delmestri, Montanari, & Usai, 2005;Reinstein & Snyder, 2005), still others have found a negative association (Hirschman & Pieros, 1985;Simonton, 2005a), or even a U-shaped curve (Wallace, Seigerman, & Holbrook, 1993). These contradictory results largely reflect the complexity of the phenomenon.…”
Section: The Criteria Intercorrelationsmentioning
confidence: 99%
“…In the US, Reinstein and Snyder (2005) focused on the information contained in reviews by two celebrated US film critics who presented their evaluations on television. We must caution that the critics whose reviews are summarised here are certainly not household names.…”
Section: Critical Reviewsmentioning
confidence: 99%
“…Second, a positive review could simply be a proxy for film quality and so critical acclaim is a predictor of film success. Reinstein and Snyder (2005) distinguish empirically between these two functions of critics. They find a small but statistically significant influencing role for ratings for dramas and small-release films offered by two high-profile film critics in the US which they identify as an influence effect, with positive reviews having a significantly larger effect on revenues than negative or mixed reviews.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation